An examination of high school students' critical thinking dispositions and analytical thinking skills - Engin Demir (Journal of Pedagogical Research, 2022)
The purpose of this correlational survey study is to examine the critical thinking dispositions and analytical thinking skills of high school students. Using a multistage cluster sampling plan, 433 students from different types of high schools completed the critical thinking disposition, and the analytical thinking skills scales. Descriptive analysis, regression analysis, and MANOVA were used to analyze the data. Research results indicated that high school students had high levels of analytical thinking skills and critical thinking dispositions. Analytical thinking skills explained 57% of the variance in critical thinking dispositions. The results suggested that having high analytical thinking skills had an impact on students' critical thinking dispositions. The results also showed that the critical thinking dispositions and analytical thinking skills of students in high performing schools were higher than those in low performing schools. Finally, mothers with higher level of education had a greater impact on students' critical thinking dispositions and analytical thinking skills.